2018
DOI: 10.4049/jimmunol.1800556
|View full text |Cite
|
Sign up to set email alerts
|

Innate T Cells Govern Adipose Tissue Biology

Abstract: Over the past 25 years, the immune system has appeared as a key regulator of adipose tissue biology and metabolic homeostasis. In lean animals, adipose-resident leukocytes maintain an anti-inflammatory environment that preserves the proper functioning of the tissue. Several adipose leukocyte classes have been described, each with unique contributions to the tissue microenvironment. Here, we describe two populations of innate T cells enriched in adipose tissue, iNKT and γδ T cells, and how they serve overlappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 97 publications
(120 reference statements)
1
23
0
Order By: Relevance
“…Studies in humans and mice have been showing the importance of immune cells resident in adipose tissue to the local and systemic metabolic homeostasis 1,2 . Macrophages are one of the populations best studied due to their involvement in metabolic diseases resulting from human obesity 1 , but other leukocyte populations present in the adipose tissue have been involved in diverse physiological functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in humans and mice have been showing the importance of immune cells resident in adipose tissue to the local and systemic metabolic homeostasis 1,2 . Macrophages are one of the populations best studied due to their involvement in metabolic diseases resulting from human obesity 1 , but other leukocyte populations present in the adipose tissue have been involved in diverse physiological functions.…”
mentioning
confidence: 99%
“…Neutrophils are also present in mouse and human adipose tissue 1,6 and may contribute to associated inflammation in obesity 7,8 . Moreover, lymphocytes have an important role in maintaining homeostasis of the adipose tissue 2,9 . On the other hand the adipose tissue can also have important contributions for the immune function 8,10 , as for example being a reservoir for memory T cells with potential to protect from infection 11,12 .…”
mentioning
confidence: 99%
“…Functionally distinct NKT cell effector subpopulations, primed to secrete unique combinations of cytokines and defined by particular transcription factor expression patterns, potently modulate disparate aspects of immunity [49][50][51][52] . In this present study, we uncovered a small population of NKT cells that expressed low levels of the transcription factor YY1.…”
Section: Discussionmentioning
confidence: 99%
“…The adipose tissue is no longer regarded as a simple organ for lipid storage, but is recognized as an endocrine organ important for metabolism homeostasis 1,2 . It has been shown that immune cell populations resident in adipose tissue have a critical role in regulation of not only local but also systemic metabolic homeostasis 3,4 . Studies in humans and mice have shown that cells like γδ and NK T cells are enriched in the adipose tissue and have an important role in maintaining its homeostasis 3,5 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that immune cell populations resident in adipose tissue have a critical role in regulation of not only local but also systemic metabolic homeostasis 3,4 . Studies in humans and mice have shown that cells like γδ and NK T cells are enriched in the adipose tissue and have an important role in maintaining its homeostasis 3,5 . These populations interact with and promote T regulatory cells (Treg), an important population for the maintenance of an anti-inflammatory environment in that tissue 3,5 .…”
Section: Introductionmentioning
confidence: 99%